Pengaruh Desain Kemasan terhadap Keputusan Pembelian Produk Biskuit dan Makanan Ringan PT Siantar Top Tbk Pada Siswa Siswi SMA Santa Lusia Bekasi - Sardoli Sinaga (PANDITA : Interdisciplinary Journal of Public Affairs, 2022)
This study aims to obtain empirical evidence regarding the effect of packaging products with indicators packaging brand, packaging images, packaging shapes and packaging colors on the buyer's decision of PT Siantar Top Tbk products on students of SMA Santa Lusia Bekasi. The data used are primary data and the student population of SMA Santa Lusia Bekasi. The sample selection method used is the probability sampling method. The total population in this study was 101 high school students from Santa Lusia Bekasi and the sample used was 50 students from SMA Santa Lusia Bekasi. Buyer's decision as the dependent variable, while the packaging brand, packaging image, packaging shape and packaging color are used as independent variables. The method used is multiple regression analysis using the SPSS program. The results of the research that have been carried out show that the packaging brand variable has a significant number of 0.030, the shape of the packaging has a significant number of 0.025 and the color of the packaging has a significant number of 0.000 which means that it partially affects the buyer's decision because it gets a number below 0.05, while the variable the packaging image has a significant number of 0.108 which means that it partially has no effect on purchasing decisions because it gets a number above 0.05, and the sour brand variable, packaging image, packaging shape and packaging color have a significant number of0.000 which means it has a simultaneous effect on the decision. buyers for getting numbers below 0.05.